Pemanfaatan Budaya Posoropu dalam Perawatan Masa Nifas oleh Perempuan Buton Utara - Usman Usman; Sapril Sapril (Media Kesehatan Masyarakat Indonesia, 2018)
The postpartum period is the period after the placenta is born and ends when the uterine devices returnlike pre-pregnancy conditions. Buton women make use of posoropu tradition as postpartum care that affects theirhealth status. This study aims to explore the utilization of posoropu tradition during the postpartum period inKulisusu District, Bonegunu District, & North Kulisusu District in North Buton Regency. A qualitative study withEthnographic approach, conducted with indepth interviews on 14 informants obtained with purposive sampling.rom the analysis of posoropu tradition during the postpartum period, consist of social aspect and cultural aspect.The social aspect of the female Buton has a self concept that the treatment performed by the Bisa (Shaman) causea magical touch, trusted, & service satisfaction in restoring the function of the reproductive organs in the past.Indentification of individuals to social groups that is the interest and habits of hereditary choose treatment doneOdhe (hatra) and “Bisa”. While the cultural aspects of postpartum care tradition that must be done, namely pidahowee musodo (hot bath), pirarai (roasted), kabongkoi (belt/belly), and drinking traditional ingredients. Viewedfrom the social aspect of the people of North Buton still maintains the traditions of the puerperium while the culturalaspects of society still cling to the culture that has been inherited by ancestors from generation to generation.